The impact of improved transport connectivity on income, education, and health: The case of the roll-on/roll-off system in the Philippines - Kris Francisco; Matthias Helble (Asian Development Bank Institute (ADBI), 2017)
This paper studies the impacts of providing an efficient and affordable transport system within a country through the experience of the Philippines. In 2003 the roll-on/roll-off (Ro-Ro) policy was implemented to provide an integrated mode of inter-island transfer. We offer three analyses that examine the effects of this policy at the household as well as the municipality level. Our first analysis shows that agricultural households largely benefit from Ro-Ro port operation, as we notice higher incomes for both agricultural and non-agricultural activities. Our results also suggest that the island location of agricultural households relative to Ro-Ro ports does not hinder the gains from the Ro-Ro policy. Meanwhile, our second analysis exhibits higher school attendance in municipalities near the Ro-Ro ports, which we observe for both males and females. Interestingly, we observe the increase much earlier in females than in males. Finally, our third analysis reveals lower household consumption of alcoholic beverages and tobacco in areas near the Ro-Ro ports. Overall, the results of our paper demonstrate several additional effects beyond economic growth of strengthening the physical linkages between the local economies within a country. More importantly, it highlights the crucial role of the transport system in a country's socio-economic development.
Keywords: O18; R20; R28; 330; roll-on/roll-off policy; agriculture; education; household expenditure